VALIDITAS E-MODUL MENULIS ARTIKEL ILMIAH BERBASIS GENRE BASED APPROACH/GBA - Afif Rofii; Ramli Ramli; Supriyati Supriyati; Imey Alviona Caesar (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research sought to validate an e-module designed to facilitate scientific article writing, grounded in the Genre-Based Approach (GBA). A quantitative survey method was employed, utilizing a Likert-scale questionnaire to gather both quantitative and qualitative data. Four experts in their respective fields were involved in the validation process, assessing the e-module's content, presentation, language, and graphic feasibility. The results of the expert validation indicated that the e-module meets the criteria for a high-quality educational tool, aligning with the needs of students and the objectives of learning scientific article writing. Specifically, the content component received an overall average score of 4.46, classified as "very valid." The remaining components—presentation, language, and graphics—each achieved an overall average score of 4.5, also categorized as "very valid." These results suggest that the developed GBA-based e-module for scientific article writing is highly valid and suitable for implementation in the Indonesian Language and Literature Education Study Program at the Faculty of Teacher Training and Education, Universitas Batanghari Jambi.